Hsa_circ_0081065 exacerbates IH-induced EndMT via regulating miR-665/HIF-1α signal axis and HIF-1α nuclear translocation - Shan Jiang; Xiaowei Xing; Ming Hong; Xingqian Zhang; Fei Xu; Guang-hao Zhang (Scientific Reports, 2024)
Abstract CircRNAs play an important role in various physiological and pathological biological processes. Despite their widespread involvement, the function of circRNAs in intermittent hypoxia (IH) remain incompletely understood. This study aims to clarify the molecular mechanism of it in IH. Differentially expressed circRNAs were identified by transcriptome sequencing analysis in intermittent hypoxia (IH) model. GO and KEGG enrichment analys were performed on the identified differentially expressed circRNAs. The circular characteristics of hsa_circ_0081065 in human umbilical vein endothelial cells (HUVECs) were detected by RT-qPCR. The sublocalization of hsa_circ_0081065 was examined by FISH. The effect of hsa_circ_0081065 on endothelial to mesenchymal transition (EndMT) was estimated by detecting the expression of EndMT related markers. Various techniques, including RNA-pull down, RIP, EMSA, dual-luciferase reporter assay and immunofluorescence staining were used to investigate the relationship among hsa_circ_0081065, miR-665 and HIF-1α. A total of 13,304 circRNAs were identified in HUVECs treatment with IH, among which 73 were differentially expressed, including 24 upregulated circRNAs and 49 downregulated circRNAs. Notably, hsa_circ_0081065 demonstrated a significantly upregulation. Hsa_circ_0081065 exhibited the circular characteristics of circRNA and was predominantly localized in the cytoplasm. Knockdown of hsa_circ_0081065 inhibited EndMT. Mechanically, we demonstrated that hsa_circ_0081065 acts as a sponge for miR-665 to up-regulate HIF-1α and exacerbate HIF-1α nuclear translocation in HUVECs. We have demonstrated that hsa_circ_0081065 is significantly upregulated in HUVECs treated with IH. Our findings indicate that hsa_circ_0081065 exacerbates IH-induced EndMT through the regulation of the miR-665/HIF-1α signal axis and facilitating HIF-1α nuclear translocation. These results provide a theoretical basis for considering of EndMT as a potential therapeutic target for OSAHS intervention.